DAYA SAING INDUSTRI TAHU - TEMPE DI KELURAHAN KLEAK KECAMATAN MALALAYANG KOTA MANADO - Anggita Hartati Sitorus; Leonardus Ricky Rengkung; Elsje Pauline Manginsela (AGRI-SOSIOEKONOMI, 2019)
This study aims to analyze the competitiveness of the "ABC" Tofu - Tempe industry and the "XYZ" Tofu - Tempe industry, Kleak Village, Malalayang District, Manado City, North Sulawesi. This research was conducted for three months from October to December 2018. The data used were primary data and secondary data. The sampling in this study was consumers from the Tahu-Tempe Industry in Kelak Village. This research uses accidentally sampling technique. Primary data collection is done by interviews using questionnaires. While secondary data was obtained from financial records from 2 Tofu - Tempe Industries in Kleak Village, skripsi from Faculty of Agriculture Library, Sam Ratulangi University (Unsrat), books available at local bookstores and the Internet through Google Scholar to access articles from various scientific journals and thesis from various universities. This study uses the Importance Performance Analysis (IPA) analysis. The results showed that the price offered by the Tofu Industry - Tempe "ABC" and Tahu - Tempe "XYZ" showed a different assessment, the industry "ABC" was considered very affordable and taste was satisfied but the quality was not satisfactory and the capacity and benefits were considered not too important. While the industry "XYZ" shows the price offered is not satisfactory from all aspects. In terms of good products for the Tofu Industry - Tempe "ABC" and Tahu - Tempe "XYZ" showed different levels of satisfaction where the "ABC" industry for consumers satisfies in terms of cleanliness and completeness but in terms of unsatisfactory cleanliness and the availability of raw materials is very unsatisfactory but for the display ofsatisfying products but considered not important for consumers, while the industry "XYZ" shows satisfying product taste but from the aspect of cleanliness, product availability and completeness in the presentation of products is very important for consumers but not satisfying while thephysical appearance of the product is less important or something expected by consumers. Then in terms of the place used by the Tofu - TempeIndustry "ABC" and the Tahu-Tempe Industry "XYZ" the level of cleanliness of the room that is still less clean, the comfort of the room that is still affordable from smoked tofu - Tempe and the noise of the engine, the physical appearance of the room is also not good and must be repairedfor the "ABC" industry, the "ABC" industry is less competitive with the industry "XYZ", while the availability of production equipment and verystrategic locations shows very satisfied and good because many tools are used and marketing locations very strategic close to boarding houses,restaurants and markets. In terms of services provided by Tahu - Tempe Industry workers "ABC" and Tahu -Tempe Industry "XYZ" both fromspeed, alertness, knowledge and friendliness have been very satisfying to consumers, only for the "ABC" industry the physical appearance ofthese workers is not good from dress and neatness that is shown to not satisfy the buyer but is very important for consumers, while for theindustry "XYZ" consumers value some already satisfactory from dress and neatness and some are unsatisfactory from dress and neatness and thisaspect is considered very important for consumers. *eprm*